The Picture Animation in Primary School. CHILDREN F1RST CINANIMA Educational Service - Fernandes, Paulo Oliveira (2017)
This paper presents the program CHILDREN F1rst, an initiative carried out by the Educational Service of CINANIMA-International Animated Film Festival of Espinho, with the support of the Ministry of Education – National Plan for Cinema, and it is destined to primary schools’ children, with the purpose of providing the contact with the animation of images and the direction of animated films in educational context.In addition to the technical issues associated with animation cinema, this program is based on pedagogical concerns and is developed with resource to methodologies of project and didactics of the animated image.In its first year (2015/2016 school year), 139 children from 7 classes of primary school were involved. At the end of the process the films were screened in two special sessions included in the programme of the 40th edition of CINANIMA and were published in DVD. These have been offered to all students, teachers and partners of this programme.